2017
DOI: 10.1080/10485252.2017.1303063
|View full text |Cite
|
Sign up to set email alerts
|

Testing independence based on Bernstein empirical copula and copula density

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Recently, Belalia et al [1] proposed to use the Bernstein empirical copula [27,33] rather than the empirical copula in the Cramér-von Mises test statistic. Moreover, they constructed new test statistics based on the Bernstein copula density estimator by Bouezmarni et al [5].…”
Section: Application: Weighted Cramér-von Mises Tests For Independencementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Belalia et al [1] proposed to use the Bernstein empirical copula [27,33] rather than the empirical copula in the Cramér-von Mises test statistic. Moreover, they constructed new test statistics based on the Bernstein copula density estimator by Bouezmarni et al [5].…”
Section: Application: Weighted Cramér-von Mises Tests For Independencementioning
confidence: 99%
“…Still, the common value of its coefficients of upper and lower tail dependence is positive and depends on the degrees-of-freedom parameter. In their numerical experiments, Belalia et al [1] found that for such alternatives, the power of the Cramér-von Mises test based on both the empirical copula and the Bernstein empirical copula is particularly weak. Their test statistics based on the Bernstein copula density estimator performed much better.…”
Section: Application: Weighted Cramér-von Mises Tests For Independencementioning
confidence: 99%
See 2 more Smart Citations
“…Most of the references cited above considered only binary status (affected/nonaffected) outcomes and ignored the ages of onset of the disease in their statistical analyses. Testing the heritability and parent-of-origin hypothesis in PsA families consists of assessing the significance of variance component parameters in a mixed effects or a copula model (Zhang & Lin, 2008;Belalia et al, 2017). However, very few of such tests are available for time-toevent outcomes.…”
Section: Introductionmentioning
confidence: 99%